Training on Applying SQ3R Reading Techniques in The Learning of Science-Social Knowledge for Elementary School Teachers in Pontianak - Djudin, Tomo; Aunurahaman, Aunurahaman; Asrori, Muhammad; Martono, Martono; Effendy, Chairil (International Journal of Public Devotion, 2024)
The target community in this PKM is elementary school teachers in Pontianak City. From the interviews, information was obtained that many teachers thought that efforts to improve their students’ abilities and skills in reading, writing and taking notes were solely the task of language teachers (Indonesian and/or English). This assumption needs to be straightened out. The dense content of teaching materials and limited face-to-face time are the reasons why many teachers do not integrate these two basic activities - reading and writing - in the classroom learning process. Teachers admitted that they rarely, if not never, train students to read using the SQ3R technique in science learning at school. This PKM activity is expected to provide additional insight for elementary school teachers in applying the SQ3R reading technique in science learning, recognizing the structure of reading texts, and making graphic post-organizer notes so that they can be applied in learning teaching materials at school. In the end, it is also hoped that the training can improve the quality of the results and processes of science and science learning in schools. Many research results conclude that learning activities that apply SQ3R are more active and the retention of learning outcomes is better (significantly different) compared to ordinary learning activities (mere lectures). This PKM training activity had been able to increase teachers' understanding of the application of the SQ3R reading technique in science and science learning in elementary schools.